The Prevalence of Metabolic Syndrome in Different Phenotypes of Pcos in Turkish Women - Ürünsak, İbrahim F; Makcakucuk, Hacer; Bahar, Leyla; Ertunc, Devrim; Tok, Ekrem C (International Journal of Innovative Research in Medical Science, 2016)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine and metabolic disorder amongst women of reproductive age, with a worldwide. Aims: The aim of this study is to investigate the percentage of Metabolic syndrome (MetS) in different phenotypes of PCOS, as well as several metabolic characteristics. Material and Methods: The study included 128 women with PCOS and 64 controls. The women were grouped into four phenotypes: hyperandrogenism (H) + chronic oligo-/anovulation (CA) + sonographic Polycystic Ovary morphology (PCOM), H-CA, CA-PCOM and H-PCO. The prevalence of MetS was determined for each group, according to the International Diabetes Foundation. Serum levels of glucose and insulin and the lipid profiles were assessed. Results: Although, the prevalence of MetS was found to be higher in H-CA and CA-PCOM phenotypes, a statistically significant difference was observed only in the classical form of PCOS. The patients with CA-PCOM and with the classical form were more insulin resistant. Fasting glucose was found to be higher in all subsets of PCOS. Serum triglyceride levels were also found higher in patients with PCOS, except for the H-PCOM phenotypes. Conclusion: According to this study, we could recommend a screening of the patients with the classical form of PCOS for MetS. An understanding of the exact etiopathogenesis and pathophysiology of PCOS in the future, might help to define the PCOS patients.